TEACHERS’ MOTIVATIONS AND EXPECTATIONS REGARDING LIFELONG LEARNING - DABIJA, Dan-Cristian; ABRUDAN, Ioana-Nicoleta; POSTELNICU, Cătălin (Studia Universitatis Babeș-Bolyai Oeconomica, 2016)
https://doi.org/10.1515/subboec-2016-0003 The global contemporary economic and social context, in constant change, makes the learning process undergo constant structural changes with profound implications. These transformations also influence practices, principles and methods used in the field of learning and teaching. The present research is focused on the motivations and expectations of teachers regarding lifelong learning. Their main motivator is to improve teaching tools, techniques and methods. The study population consists of educators who teach Romanian language and literature to national minorities (Hungarian, German, Roma, Tatar, Serbian, Ukrainian, etc.) and to migrants from various states. The respondents have participated in a lifelong learning program. JEL Classification: I26, I29, M31, M53